Constraints on the Nonstandard Interaction in Propagation from Atmospheric Neutrinos. (1st October 2015) - Fukasawa, Shinya; Yasuda, Osamu
Abstract : The sensitivity of the atmospheric neutrino experiments to the nonstandard flavor-dependent interaction in neutrino propagation is studied under the assumption that only nonvanishing components of the nonstandard matter effect are the electron and tau neutrino componentsϵ e e, andϵ e τ, ϵ τ τ and that the tau-tau component satisfies the constraintϵ τ τ = | ϵ e τ | 2 / ( 1 + ϵ e e ) which is suggested from the high energy behavior for atmospheric neutrino data. It is shown that the Super-Kamiokande (SK) data for 4438 days constrains| t a n β | ≡ | ϵ e τ / ( 1 + ϵ e e ) | ≲ 0.8 at 2.5σ (98.8%) CL whereas the future Hyper-Kamiokande experiment for the same period of time as SK will constrain as| t a n β | ≲ 0.3 at 2.5σ CL from the energy rate analysis and the energy spectrum analysis will give even tighter bounds onϵ e e and| ϵ e τ | .